Perbandingan Kewenangan Menyatakan Keadaan Darurat Antara Indonesia, Prancis dan Malaysia - Yusriel Bachrie; Jadmiko Anom H; Sri Wahyuni (Legal Spirit, 2023)
The state is obliged to declare a state of emergency if it feels threatened by danger, whether coming from outside or within the country. Implementation of check and balance is necessary because executive authority in a state of emergency is too broad and open. Mechanism is needed that limits executive authority aimed at reducing the potential for the executive to abuse power in the implementation of a state of emergency. This study aims to determine the dangers of a single executive authority in imposing a state of emergency in the Indonesian Constitution by using legal arrangements and practices in France and Malaysia. This article uses normative legal research that based on library-based source. The approach used by researchers is a comparative approach that compares the content of provisions in the constitution and compares the implementation and history of emergency regulations. The result of this study is that the implementation of check and balance for the executive in determining a state of emergency is really needed based on a comparison of regulations and legal practices in France and India. Therefore, Indonesia must implement the practice of check and balance in declaring a state of emergency in order to decrease any potential of abuse of power.